2022
DOI: 10.1101/2022.01.24.477459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type diversity in a developing octopus brain

Abstract: Octopuses are mollusks that have evolved intricate neural systems comparable with vertebrates in terms of cell number, complexity and size. The cell types within the octopus brain that control their amazingly rich behavioral repertoire are still unknown. Here we profile cell diversity of the paralarval Octopus vulgaris brain to build a comprehensive cell type atlas that comprises mostly neural cells, as well as multiple glial subtypes, endothelial cells and fibroblasts. Moreover, we spatially map cell types wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
5
9
0
Order By: Relevance
“…However, their swimming and predatory behavior becomes more refined with age (Darmaillacq et al, 2014; Villanueva et al, 1997), which may be reflected in the possible maturation process that we observe. Interestingly, two recent preprints (Duruz et al, 2022; Styfhals et al, 2022) describe the cell types in the head of hatchling and embryos of two distinct cephalopod species, and their cell clustering, show similarities with what we observe in the optic lobe at the hatchling stage. Such a change in cell type complement is reminiscent of the situation reported in the Drosophila ‘optic lobe’ which is not related either evolutionarily or embryologically to the cephalopod optic lobes (Ma et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…However, their swimming and predatory behavior becomes more refined with age (Darmaillacq et al, 2014; Villanueva et al, 1997), which may be reflected in the possible maturation process that we observe. Interestingly, two recent preprints (Duruz et al, 2022; Styfhals et al, 2022) describe the cell types in the head of hatchling and embryos of two distinct cephalopod species, and their cell clustering, show similarities with what we observe in the optic lobe at the hatchling stage. Such a change in cell type complement is reminiscent of the situation reported in the Drosophila ‘optic lobe’ which is not related either evolutionarily or embryologically to the cephalopod optic lobes (Ma et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, the respective protein can be secreted, which means that mRNA could be detected in a different location than the protein. Our data confirmed previous findings using HCR v3.0 on transverse sections ( Deryckere et al, 2021 ; Styfhals et al, 2022 ) and showed the power of this technique to map marker gene expression in 3D during organogenesis.…”
Section: Introductionsupporting
confidence: 91%
“…Ov-elav expression visualized the central brain masses, optic lobes, stellate, mouth and gastric ganglia as well as the neurons in the arms, while Ov-apolpp was mainly expressed within the neuropil located in the central brain, optic lobes and arms (Figure 3). The expression of Ov-elav and Ov-apolpp observed in whole mount octopus embryos matches the expression data seen on transverse sections (Deryckere et al, 2021;Styfhals et al, 2022). The z-stack overview and 3D view of the multiplexed HCR of Ov-elav and Ov-apolpp is provided in the Supplementary Information (Supplementary Video V2-4).…”
Section: Multiplexing In Situ Hybridization Chain Reactionsupporting
confidence: 68%
“…We also include immunohistochemistry to prove that sequential detection of mRNA and protein is feasible using our combined method. Our data confirmed previous findings using HCR v3.0 on transverse sections (Deryckere et al ., 2021; Styfhals et al ., 2022) and showed the power of this technique to map phases of organogenesis in 3D.…”
Section: Introductionmentioning
confidence: 99%